2010
DOI: 10.4018/jicte.2010070104
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses’ Perception on the Impact of Information Technology on Teaching and Learning

Abstract: This paper investigates student nurses’ perceptions of the impact of using information technology (IT) on teaching and learning critical care nursing. This study was conducted at the Faculty of Nursing, Mansoura University, Egypt. The sample included 163 of fourth year Bachelor of Nursing students enrolled in a critical care nursing course during the first semester of the academic year 2007-2008. The data was collected using a questionnaire sheet that gathered information about student nurses’ IT skills and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…One of the non‐material elements is the nursing standards of practice required for HIT content to be integrated into the curriculum. However, student learning outcomes on this topic essentially rely on faculty members' competency and advanced knowledge in the use of HIT (Fetter ; Kandeel & Ibrahim ). One of the barriers preventing the integration of HIT (such as EHRs) into health professional education is a shortage of faculty members who are familiar with different types of EHRs (Borycki et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the non‐material elements is the nursing standards of practice required for HIT content to be integrated into the curriculum. However, student learning outcomes on this topic essentially rely on faculty members' competency and advanced knowledge in the use of HIT (Fetter ; Kandeel & Ibrahim ). One of the barriers preventing the integration of HIT (such as EHRs) into health professional education is a shortage of faculty members who are familiar with different types of EHRs (Borycki et al.…”
Section: Discussionmentioning
confidence: 99%
“…The revolution in computer technology that transformed HIT has become a required part of nursing education (Kandeel & Ibrahim ). This fact drives faculty members to adopt HIT software and integrate it into teaching and learning methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alignment with the present study, Kivuti Wanjuki & Chepchirchir (2011) Osborne ( 2011) as they mentioned that information literacy is perceived as a major part of a nurse's professional role . Kandeel & Ibrahim( 2010), Kivuti Wanjuki & Chepchirchir ( 2011), Kipturgo et al ( 2014) as they reported that nursing students had a positive perception of the impact of using information technology education and health care, which indicate student readiness for nursing informatics education. Furthermore, study results declared that nursing students educational needs of nursing informatics include: application of informatics in education, telemedicine, ethical application in nursing ……etc.…”
Section: Discussionmentioning
confidence: 99%
“… Inadequate ICT facilities: Equipping schools with sufficient computers, tablets, or other ICT devices is essential. The research by Adomi and Kpangban (2010) highlights the lack of these resources as a significant barrier, and this is corroborated by the reports of Ajayi and Ekundayo (2009), Department of Education and Science (2008), Bartlett al (2013), Oguegbu (2016), Adeyemo (2010), and Abdulkadir et al (2014.…”
Section: Infrastructure Constraintsmentioning
confidence: 84%